Study of threats to economic security and countries in the context of globalization - Vorvul, A. S.; Vorvul, Yu. V.; Pererva, P. G. (My University, 2023)
It is proved that globalization is a new level of economic activity, operating in a single economic space. Globalization is characterized by the predominance of world economic relations over national ones. Globalization is a factor in the strengthening of traditional and the emergence of new threats to the economic security of the state and is found in all indicators and indicators of economic security.
Дослідження загроз економічній безпеці країни та країни в умовах глобалізації
Keywords: globalization; economic security; threats; factors; indicators